Profil Fisiologis Pascapemberian Katuk Depolarisasi untuk Peningkatan Produktivitas Sapi Pedaging - Ronald Tarigan; Afton Atabany; Fadjar Satrija; Muladno Muladno; Nofriyandi Hanif; Agik Suprayogi (Jurnal Ilmu Pertanian Indonesia, 2023)
Katuk (Sauropus androgynus), a traditional herb that has been traditionally consumed by breastfeeding mothers to increase their milk production but still has some side effects, such as bronchiolitis obliterans and inhibition of calcium absorbtion. Removing the polar compounds in katuk leaf (depolarized katuk leaf) can eliminate those side effects without eliminating its side effect in increasing milk production and body growth in several production animals. This study was aimed to analyze the physiological status of beef cows consuming diet supplemented with depolarized katuk leaf as feed additive by measuring their hematology and blood mineral profile. Nine Brahman cross cows in the finisher stage, were grouped based on their diet: complete feed (control), complete feed plus depolarized katuk leaf powder (P1; 100 g per day), and complete feed plus depolarized katuk leaf pellet (P2; 100 g per day). Blood sample was collected after six weeks of consumption for analysis of hematological profiles including total erythrocytes, hematocrit, hemoglobin, total leukocytes, stress index (neutrophil-lymphocyte ratio); and blood mineral concentration (calcium and phosphorous). Dietary administration of depolarized katuk leaf did not have any statistically significant effect on all hematology parameters and blood mineral profiles. In conclusion, depolarized katuk leaf can be used as a growth promoter in beef cows without any negative effect on their physiological status. Keywords: Hematologi, katuk depolarisasi, kesehatan, mineral, sapi pedaging